Satellite-based tracking of agricultural adaptation progress - Reymondin, Louis; Golden, Aaron; Spillane, Charles (2022)
Lack of systematic tools and approaches for measuring climate change adaptation limits the measurement of progress toward the adaptation goals of the Paris Agreement. To this end, we piloted a new approach, the Biomass Climate Adaptation Index (Biomass CAI), for measuring agricultural adaptation progress in Ethiopia across multiple scales using satellite remote sensing data. The Biomass CAI can monitor agri-biomass productivity associated with adaptation interventions remotely and facilitate more tailored precision adaptation. The Biomass CAI focuses on decision-support for end-users to ensure that the most effective climate change adaptation investments and interventions can be made in agricultural and food systems.